Nipocalimab, an anti-FcRn monoclonal antibody, in participants with moderate to severe active rheumatoid arthritis and inadequate response or intolerance to anti-TNF therapy: results from the phase 2a IRIS-RA study - Taylor, PC; Schett, G; Huizinga, TW; Wang, Q; Ibrahim, F; Zhou, B; Liva, SG; Shaik, JSB; Xiong, Y; Leu, JH; Panchakshari, RA; Loza, MJ; et al. (BMJ Publishing Group, 2024)
Objectives: To investigate the efficacy, safety, pharmacokinetics and pharmacodynamics of nipocalimab in participants with moderate to severe active rheumatoid arthritis (RA) and inadequate response or intolerance to ≥1 antitumour necrosis factor agent.